The Role of Petok D Documents in Recognizing Community Rights to Land: A Case Study in Cabak Village - Peggy Anggun Adelia Putri (Faculty of Law, Universitas Negeri Semarang, 2025)
Legal uncertainty surrounding land ownership based solely on Petok D documents, which are often not recognized within the formal land administration system, has the potential to cause agrarian conflicts involving companies, the government, or local residents. This study employed a qualitative approach with empirical juridical research methods, utilizing interviews, observations, and document analysis. The data collected were analyzed and presented descriptively. The results show that the community in Desa Cabak still heavily relies on Petok D as the basis for land ownership claims; however, these documents do not always meet the administrative requirements for land certification. There is also a significant gap between customary law and state law, making it difficult for the community to obtain legal certainty. Additional challenges include limited public understanding of legal procedures, overlapping land policies, and weak legal protection for non-certificate ownership evidence. The study concludes that affirmative policies and more inclusive regulatory reforms are needed to accommodate the social realities of communities with longstanding customary land rights. A comprehensive solution could strengthen the legal position of the community and help prevent future agrarian conflicts.